Effectiveness of the Educational Protocol Derived from the Model of Examining the Harms of Families of Veterans with Post-Traumatic Stress Disorder on the Performance and Hardiness of These Families in Kermanshah Province - GoliGarmkhani , Rahim; Amiri, Hassan; Golmohammadian , Mohsen (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This research aimed to examine the effectiveness of an educational protocol derived from the model of examining the harms of families of veterans with post-traumatic stress disorder on family hardiness and performance.Methods and Materials: This research was a quasi-experimental study with a pre-test - post-test control group design and is classified as applied research in terms of its objectives. The statistical population of this study included all spouses and children of veterans with post-traumatic stress disorder in Kermanshah province. Sixty individuals were selected as the sample in a convenient manner and randomly divided into two groups: experimental and control. The experimental group received training according to the educational protocol derived from the model over nine 90-minute sessions for two and a half months, while the control group received no intervention during this period. The research tools were the Family Assessment Device (FAD) and the McCubbin Family Hardiness Index (FHI) questionnaires, which were administered in three stages: pre-test, post-test, and follow-up, to collect data.Findings: Data were analyzed using repeated measures analysis of variance. The results of the repeated measures ANOVA indicated that the educational protocol derived from the model has an effect on the performance and hardiness of families of veterans with post-traumatic stress disorder, with a significant difference between the post-test scores of the experimental and control groups.Conclusion: Based on the findings of this research, it is recommended to use the model derived from the pattern of examining the harms on the performance and hardiness of families of veterans with post-traumatic stress disorder to reduce the harms of these families.